SNS Carbon Bed Research Project Design, Commissioning, and Initial Results. Issue 1 (1st May 2022) - DeGraff, B; Barnhart, D; Gold, S; Howell, M; Kim, S; Kraft, D; McMahan, C; Moore, L; Neustadt, T; Vandygriff, D J; Vandygriff, D M
Abstract: The Spallation Neutron Source (SNS) at Oak Ridge National Laboratory (ORNL) has three operating cryogenic facilities: Central Helium Liquefier (CHL), Cryogenic Test Facility (CTF) and Cryogenic Moderator System (CMS). All three systems use vessels filled with activated carbon as the final major component to remove oil vapor from the compressed helium circuit prior to insertion into the system's cryogenic cold box. However, different versions of carbon are used in different systems. A skid was designed which contains two separate carbon containing vessels for the purpose of comparing the relative efficacy of different versions of carbon filtration media. The design, fabrication, installation, commissioning, and initial results of this dual-bed test skid will be presented. Future testing plans utilizing different filter media will also be discussed.